Stereoselective Metabolism by Human Liver CYP Enzymes of A Substituted Benzimidazole - Äbelö, Angela; Andersson, Tommy B.; Bredberg, Ulf; Skånberg, Inger; Weidolf, Lars (Drug metabolism and disposition, 2000)
H 259/31 is a substituted benzimidazole developed as a structural analog of omeprazole. Metabolites of H 259/31 formed in human liver microsomes were identified by using the synthetic reference compounds and liquid chromatography/mass spectrometry. The predominant metabolic pathways found include oxidation of the sulfoxide to sulfone, oxidative O-dealkylation of the cyclopropylmethoxy group to the corresponding pyridone and aromatic hydroxylation to give the phenolic derivative. Stereoselectivity in the metabolism of the enantiomers of H 259/31 was demonstrated in human liver microsomes. The sum of the formation intrinsic clearances of all three metabolites was higher for the S-enantiomer than that of the R-form, indicating that the S-enantiomer is eliminated more rapidly. It was also shown in the present study that the sulfone metabolite is subject to additional metabolism, which should be taken into account when determining the intrinsic clearance for formation of metabolites and when the relative importance of metabolic pathways is determined. Expressed enzymes indicate major involvement of cytochrome P-450 (CYP) 2C19 in the formation of the hydroxy derivative as well as in pyridone formation from the enantiomers of H 259/31. CYP3A4 and CYP2C9 seem to contribute as low-affinity enzymes in both reactions. The sulfone metabolite was formed mainly from CYP3A4. Stereoselectivity in CYP3A4-, CYP2C19-, and CYP2C9-mediated metabolic pathways was demonstrated.